Assessing matting patterns, chromosome composition, host suitability, and diapause expression of Euschistus (Hemiptera: Pentatomidae) strains and species - Hickmann, Frederico (2023)
Brazil has emerged as a prominent player in the global crop production industry, significantly contributing to the global food supply. Land use and agricultural practices are important factors in determining which arthropods, native or invasive, will positively or negatively impact agroecosystems from a human perspective. Stink bugs are a common insect group in Brazil that feeds on crops, causing a decrease in yield and quality. For instance, the Neotropical brown stink bug, Euschistus heros (Fabricius), a rare species in soybean fields in the seventies, quickly evolved into a key soybean pest in a few decades. Furthermore, E. heros has become a significant threat to cotton crops recently. The discovery of two distinct strains of E. heros in Brazil, with a secondary contact area in central Brazil, raised questions about their impact on pest dynamics in Brazil. Moreover, in the Neotropics, several species of Euschistus have been recorded on soybean, but only one has become highly prevalent in soybean fields. Thus, this study aimed to investigate the reproductive isolation and asymmetrical gene flow between the two allopatric E. heros, characterize the meiotic behavior, microsatellite accumulation, and satDNA of the two strains of E. heros and their hybrid progeny, and compare with sibling species E. crenator (Fabricius) and E. taurulus Berg, characterize the host preference and host suitability of the two E. heros strains and their reciprocal hybrids. Additionally, we test the suitability of soybean and cotton and susceptibility to selected insecticides of three Euschistus species (E. heros natural hybrid population, E. taurulus, and E. crenator) reported on soybeans in Brazil. Moreover, we characterize the diapause expression/termination of E. heros (both strains), E. taurulus, and E. crenator. Finally, we employed a functional and molecular approach to characterize the transcriptome profile of E. heros and E. taurulus subjected to different photoperiod conditions, functionally validating the candidate genes in E. servus, a Nearctic species. We identified that the SS strain is larger and darker, whereas the NS strain is smaller and has a lighter brownish color. Furthermore, we found that E. heros mates assortatively with bigger insects, favoring SS and reciprocal hybrids (NS females mated with SS males) had a reduced frequency of chiasmata. In addition, the satDNAs were differentially accumulated, mainly on the Y chromosome, in the two strains of E. heros. Our bioassays and trials revealed that the SS strain chose soybean over cotton, whereas the NS strain chose soybean and cotton evenly. The reciprocal hybrid strains (HSN and HNS) behaved similarly to NS, choosing randomly between cotton and soybean. Nymph survivorship of the pure strains and their reciprocal hybrids was similar when fed on soybean, whereas only reciprocal hybrids reached adulthood when fed on cotton, although with very low viability. We identified that a soybean-based diet significantly improved the biological parameters of E. heros compared to the sibling species. Soybean was found to be moderately suitable for E. crenator, while E. taurulus showed low suitability for the same; in contrast, cotton branches are unsuitable for all three species. Additionally, the insecticide susceptibility of E. heros, E. crenator, and E. taurulus to organophosphates and pyrethroids showed low variation. The diapause expression varies significantly among Euschistus strains and species (strong in E. taurulus, moderate in E. heros SS, weak in E. heros NS, and absent in E. crenator). Moreover, the short daylength and lower temperature combination increased diapause expression and delayed diapause termination in E. heros (both strains). Through transcriptomic profiling of diapausing and non-diapause E. heros and E. taurulus, we identified and validated the genes ftz-f1, fpps, and jheh genes significantly contribute to ovary development, and ftz-f1 reduces lipid storage of the Nearctic species E. servus. Our findings suggest that E. heros pest dynamics are majorly related to the introduction of soybean crops in South America. Although we identified that the two strains show only minor differences, the asymmetric introgression can be related to mating and meiosis behavior; reuniting these two genetic pools with no apparent reproductive barrier can increase variability and select more suitable pest phenotypes. Additionally, the diapause expression of the two strains suggests that it could contribute to the pest outbreaks in the cotton crop. Among the Euschistus species tested, we identified a conserved genome structure and a similar insecticide susceptibility. However, soybean suitability and diapause expression are distinct. Finally, our molecular approach revealed that the diapause of Euschistus is related to JH signaling and oogenesis arrest that appears to be regulated by the ftz-f1 gene. With these answers, we take a step further to understand the implication of the Euschistus strains (both E. heros strains and the species E. taurulus and E. crenator), providing unedited evolutionary and biological information and supporting the development of strategies and tactics for the management of this pest species in the Brazilian agroecosystems.